PENGGUNAAN MODEL PERMAINAN SUSUN GAMBAR DALAM MENULIS KALIMAT SISWA SD KELAS 3 - Rissa Beatrik (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2015)
This paper describes model of teaching writing for elementary school students using Picture and Picture techniques.  As to write a complete sentence in Bahasa Indonesia, is the core competency for elementary school students in the grade 3 according to 2013 Curriculum for SD, model of appropriate teaching is required to explore.  This model is a response to alternate conventional methods to accomplish Standardized Competency.  This model promotes games-based interactive model to arouse writing sentences in a competition rules and drive interest to students.